A new method for defining the ploughing forces in processing of brittle materials with the formation of discontinuous chips. (22nd February 2022) - Popov, Alexey
When monitoring cutter wear during microcutting, it is necessary to consider the ploughing force of the tool flank face (PFs). The method of measurement differs based on the wear of the cutting tools and cannot be applied to determine PFs. When we cut brittle materials using a tool with wear there are significant fluctuations in the cutting forces due to the unstable chip formation, so the cutting forces cannot be measured. A new method for defining PFs when cutting brittle materials with the formation of discontinuous chips has been proposed in this study. The reliability of the new method has been confirmed by comparing PFs obtained with the help of different methods of cutting materials with the formation of continuous chips.